Prevalence of goitre, iodine uptake and salt iodization level in Mahasamund district of Chhattisgarh: a baseline study in Central India - Sinha, Ashish K.; Sharma, Hemant; Panda, Prem S.; Chandrakar, Aditi; Pradhan, Somen K.; Dixit, Srishti (International Journal of Research in Medical Sciences, 2017)
Background: Iodine deficiency disorder (IDD) is the single most important preventable cause of brain damage. Iodine deficiency disorders (IDDs) refer to all of the consequences of iodine deficiency in a population, which can be prevented by taking adequate amount of Iodine. The objectives was to ascertain the prevalence goitre among 6-12 year children by clinical examination in Mahasamund district; 2) to document the iodine uptake status reflected by random urinary excretion levels in a sub-sample of 6-12 year children covered for clinical examination, and 3) to evaluate the coverage of iodized salt at community level (i.e. at household and retail shop) on-the-spot test by using rapid salt testing kit. Methods: A cross sectional community based survey was done in Mahasamund district during April 2015 to September 2015. The study population was children in the age group of 6-12 years. 30 cluster sampling methodology was applied using PPS sampling technique, based on latest survey guidelines of NIDDCP of Govt. of India. The parameters studied were prevalence of goitre, urinary iodine excretion, and iodine content in salt at community level (i.e. household and shop). Results: A total of 2700 children aged from 6-12 years were assessed clinically for goitre. The total goitre prevalence was 4.29% (95% CI: 3.3-5.27). The median urinary iodine excretion (MUIE) was 106.67μg/L (range 11-216.7μg /L) among surveyed children. 37.4% of the urinary iodine excretion values were <100 μg/L. The households consuming inadequately iodized salt (i.e. iodine content ≤15 ppm) was 20% in the surveyed district. Conclusions: Although prevalence of goitre and median urinary iodine excretion among surveyed population was found satisfactory against the norms set by NIDDCP in surveyed district but universal salt iodization (USI) is yet to achieve in surveyed district.